Karakterisasi Dan Potensi Pengolahan Ampas Sagu Menjadi Briket - Cahyani, Anugrah; Andrio, David; Darmayanti, Lita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Sago pulp is a waste from the sago starch industry. Sago pulp has not been used optimally and a small portion is used as animal feed, the rest is dumped into reservoirs or around rivers where sago is processed which can pollute the environment. Sago pulp can be used as solid fuel in the form of briquettes. This study aims to investigate the characteristics of sago pulp and analyze the potential for processing sago pulp into briquettes. The result showed the calorific value of sago pulp was 3383,51 cal/g. This result indicates that sago pulp can be used as a raw material for briquettes. Keywords: sago pulp, briquettes